1982
DOI: 10.1073/pnas.79.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of actomyosin ATPase by vanadate.

Abstract: Actin-myosin subfragment-l (SF-1) or actin-heavy meromyosin is dissociated by the binding of ADP and vanadate (Vi) A recent study demonstrated the inhibition of myosin ATPase activity by vanadate (Vi) (1). The formation of an extremely stable myosin-ADP-vanadate complex (t112 of 1-2 days) provides an explanation of the mechanism of inhibition. Further studies to be published elsewhere have shown that the normal myosin-ADP complex binds vanadate weakly and undergoes a slow isomerization to form a stable comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
82
2

Year Published

1982
1982
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 14 publications
7
82
2
Order By: Relevance
“…Enzymatic studies of dynein (45,47,58) and other ATPases (20,41) have concluded that vanadate does not prevent either the ATP binding or ATP hydrolysis steps of the ATPase cycle. However, an ADP.V complex forms that cannot be released from the enzyme, preventing further rounds of hydrolysis.…”
Section: Outer-arm Conformations In Nonmotile Ciliamentioning
confidence: 99%
“…Enzymatic studies of dynein (45,47,58) and other ATPases (20,41) have concluded that vanadate does not prevent either the ATP binding or ATP hydrolysis steps of the ATPase cycle. However, an ADP.V complex forms that cannot be released from the enzyme, preventing further rounds of hydrolysis.…”
Section: Outer-arm Conformations In Nonmotile Ciliamentioning
confidence: 99%
“…In the presence of actin, the rate of vanadate release increases by 10 5 compared to that of M‚ADP‚V 1 alone (5 × 10 -6 s -1 ) (11). Although the actin-stimulated myosin ATPase activity has been described to be about 90% inhibited by ADP‚V 1 (12), it was suggested that this inhibition could be due in part to the presence of polymeric vanadate ions, because high vanadate concentrations (> 900 µM) are needed (13). In fact, it has been suggested that tetrameric vanadate (V 4 ) interacts with myosin, being responsible for the vanadate-induced photolytic cleavage of myosin subfragment 1 (14,15).…”
mentioning
confidence: 99%
“…V; blocks the myosin and actomyosin ATPase reactions by forming a stable M -ADP -V; complex (Goodno, 1979). This intermediate dissociates very slowly (rate constant~z2.5 x 10-6 s-', Goodno, 1982), but binding to actin promotes V; and ADP release (Goodno and Taylor, 1982). V; also suppresses the contraction of skinned muscle fibers (Goody et al, 1980 ;Magid and Goodno, 1982).…”
Section: Introductionmentioning
confidence: 99%